Analisis Model Pendidikan Tauhid di Pesantren al-Ikhlash Lamongan - Muhammad Hambal Shafwan; Din Muhammad Zakariya (TSAQAFAH, 2021)
This study aims to explore how the thoughts of the director and the teachers of al-Ikhlash Islamic Boarding School about tauẖîd education, and how the implementation of tauẖîd education in al-Ikhlash Lamongan Islamic Boarding School. The approach used in this research is a qualitative approach with a type of phenomenology. The results showed that: First, tauẖîd received special attention at al-Ikhlash Islamic Boarding School because the main target of education in this Islamic boarding school was the formation of a generation of Muslims who had pure monotheism that colored their entire life, because the concept of monotheism contains doctrinal implications that the purpose of human life must be within the framework of worshiping Allah and from this concept of monotheism will emerge moral standards. Second, tauẖîd education at al-Ikhlash Islamic Boarding School uses the 3P method, namely doctrine values of tauẖîd, understanding, and practice. This is because tauẖîd education has more to do with things that are unseen which require that faith be prioritized over reason in order to become individuals who fear Allah. While the tauẖîd learning method at Pesantren al-Ikhlash Lamongan uses the halaqah system in the mosque by studying the monotheistic books written by Muhammad bin Abdul Wahab and also the learning system in the classroom by studying the monotheism books written by Dr. Salih Fauzan.